Effects of insulin-like growth factor binding protein 3 on cell growth and tumorigenesis in oral squamous cell carcinoma - Xu, Hong-Yuan; Zhu, Dong-Wang; Zhong, Lai-Ping; Zhang, Zhi-Yuan; Yang, Cheng-Zhe; Yang, Xiao; Zhang, Peng (Translational Cancer Research; Vol 8, No 5 (September 30, 2019): Translational Cancer Research, 2019)
Background: This study was performed to investigate the effect of insulin-like growth factor binding protein 3 (IGFBP3) on the biological behavior of tumor cells and tumorigenesis of oral squamous cell carcinoma (OSCC). Methods: OSCC HB96, CAL27, and Tca8113 cells were transfected with the following plasmids: siRNA-IGFBP3, pcDNA-0-IGFBP3, or siRNA-NC (negative control). The effect of aberrant IGFBP3 on cell viability, apoptosis, and colony formation was assessed. Quantitative real-time PCR (qRT-PCR) and western blot analysis were used to measure IGFBP3 mRNA and protein levels, respectively. HB96 and CAL27 cells were transfected with IGFBP3-expressing lentiviral plasmids and then transplanted into nude mice to monitor xenograft tumor formation. Results: An optimal transfection efficiency was obtained with 50 pmol siRNA-IGFBP3. Transient silencing of IGFBP3 significantly reduced cell viability, and increased apoptosis in comparison with the non-targeting negative control (NC). Overexpressing IGFBP3 promoted cell viability. Additionally, in comparison with the NC group, both cell growth and colony formation were reduced, while apoptosis was elevated in stably transfected cells. Moreover, silencing IGFBP3 inhibited cell viability and tumor formation in nude mice after 3 weeks, and colony formation, diminished tumorigenesis in nude mice, but promoted cell apoptosis in OSCC cells. Conclusions: Collectively, our study revealed a protumorigenic role for IGFBP3 in OSCC cancer cells, and demonstrated a potential mechanism for the dysregulation of IGFBP3 in cell growth. Therefore, IGFBP3 may be a potential therapeutic target for the treatment of OSCC.